Modeling Emulsification Influence on Oil Properties and Fate to Inform Effective Spill Response - French-McCay, Deborah P.; Frediani, Matthew; Gloekler, Melissa D. (Frontiers in Environmental Science, 2022)
Water-in-oil emulsification affects spilled oil fate and exposure, as well as the effectiveness of oil spill response options, via changes in oil viscosity. While oil weathering processes such as evaporation, dissolution, photo-oxidation, and biodegradation increase oil viscosity about 10-fold, incorporation of water droplets into floating oil can increase viscosity by another order of magnitude. The objective of this study was to evaluate how changes in viscosity by oil type, with weathering, and with emulsification affect oil fate. Oil spill modeling analyses demonstrated that the increase in viscosity from emulsification prolonged floating oil exposure by preventing the oil from dispersing into the water column. Persistent emulsified oils are more likely to come ashore than low viscosity oils that readily disperse. Through a rapid increase in viscosity, emulsification restricted entrainment and slowed evaporation. Water column exposure to dissolved concentrations increased with lower viscosity oils. Thus, the ability to emulsify, and at what weathered state, are important predictors of oil fate. Oil viscosity is an important consideration for choosing response alternatives as it controls effectiveness of mechanical removal, in-situ-burning and surface-active chemicals. Therefore, understanding and quantification of oil emulsification are research priorities. The most influential model input determining emulsification and the emulsion’s viscosity is its maximum water content, as it controls the ultimate viscosity of the emulsion. Viscosities were also influenced by the volatile content and initial viscosity of the oil. Algorithms quantifying emulsion stability under field conditions have not been developed, so emulsions were assumed stable over the 30-day simulations. Changes in emulsion stability over time would affect oil properties and so floating oil and shoreline exposures, as well as response effectiveness. However, water column exposures to dissolved concentrations are determined within a few days of oil release, and as such would not be affected by differences in long-term stabilities of the emulsions.